2007
DOI: 10.2741/2086
|View full text |Cite
|
Sign up to set email alerts
|

The role of the granulocyte colony-stimulating factor receptor (G-CSF-R) in disease

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a key regulator of granulopoiesis via stimulation of a specific cell-surface receptor, the G-CSF-R, found on hematopoietic progenitor cells as well as neutrophilic granulocytes. It is perhaps not surprising, therefore, that mutations of the G-CSF-R has been implicated in several clinical settings that affect granulocytic differentiation, particularly severe congenital neutropenia, myelodysplastic syndrome and acute myeloid leukemia. However, other studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 116 publications
3
28
0
2
Order By: Relevance
“…40 NFI-A is a novel negative transcriptional regulator of G-CSFR expression, which plays a crucial role in the production and function of granulocytes. 41 Knockdown of NFI-A in E culture led to activation of G-CSFR, whereas NFI-A transduction in G culture blocked the receptor expression. We found that NFI-A binds to a cis-element located between nucleotides Ϫ318 and Ϫ334 in the G-CSFR promoter and represses its transcription in reporter and functional assays.…”
Section: Discussionmentioning
confidence: 98%
“…40 NFI-A is a novel negative transcriptional regulator of G-CSFR expression, which plays a crucial role in the production and function of granulocytes. 41 Knockdown of NFI-A in E culture led to activation of G-CSFR, whereas NFI-A transduction in G culture blocked the receptor expression. We found that NFI-A binds to a cis-element located between nucleotides Ϫ318 and Ϫ334 in the G-CSFR promoter and represses its transcription in reporter and functional assays.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 Rarely, somatic or de novo heterozygous CSF3R mutations in the extracellular region of the G-CSFR have been described. [17][18][19][20] These mutants are characterized by hyporesponsiveness to rhG-CSF and act in a dominant-negative fashion by interfering with proper function of the wild-type (WT) G-CSFR. Additionally, a heterozygous germline CSF3R mutation has been associated with neutrophilia.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a number of GCSFR mutations have been characterized in patients with severe congenital neutropenia, and blastic cells containing these mutations can progress to myelodysplastic syndrome and acute myeloid leukemia. 10 Importantly, GCSF is used therapeutically to stimulate granulopoiesis in patients with congenital, chemotherapy-induced, and radiationinduced neutropenia to prevent life-threatening infections, as well as for mobilization of hematopoietic stem and progenitor cells (HSPCs) from their niche in the bone marrow for harvesting and transplantation. 11 Gcsf was first purified and characterized in mice 3,5 and subsequently identified in a number of other nonmammalian vertebrates, including chicken (Gallus gallus), 12 Japanese flounder (Paralichthys olivaceus), 12 fugu (Takifugu rubipes), 12 green spotted pufferfish (Tetraodon nigroviridis), 12 and zebrafish (Danio rerio).…”
Section: Introductionmentioning
confidence: 99%